2011
DOI: 10.17221/16/2010-rae
|View full text |Cite
|
Sign up to set email alerts
|

Content changes of adsorbable organically bound halogens during sludge centrifugation and drying

Abstract: A wastewater treatment plant in Brno may be one of the wastewater treatment plants in the Czech Republic using a dryer for dewatering the sludge. The results of an adsorbable organically bound halogens balance analysis measured on the sludge dryer at the waste water treatment plant in Brno are demonstrated in this work. The aim of this work was to calculate the material balance in the treatment process (centrifugation and drying). Control places were chosen and then samples of water and sludge (at the inlet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Among other alternative methods of AOX determination, spectroscopy with plasma emission detector (PED) [96], gas chromatography coupled with mass spectrometry (GC/MS) [97], ion chromatography (IC) [98], combustion ion chromatography (C/IC) [99], combustion-microcoulometry, combustion ion chromatography titration [100], ultrasonic extraction-high temperature combustion absorption-ion chromatography [101], neutron activation analysis (NAA) [102,103], inductively coupled plasma mass spectrometry (ICP/MS) [104], inductively coupled plasma atomic emission spectroscopy (ICP/AES) [105], liquid chromatography coupled with mass spectrometry (LC/MS) [106], precursor ion scan of triple quadrupole mass spectrometry (PIS of QqQ MS) [79] and flow injection analysis (FIA) [107,108] have been utilized. The wide application of NAA, GC/MS, LC/MS, ICP/MS and ICP/AES is not regulated by legislation because of the high cost and skill level required.…”
Section: Determination Of Aoxmentioning
confidence: 99%
See 2 more Smart Citations
“…Among other alternative methods of AOX determination, spectroscopy with plasma emission detector (PED) [96], gas chromatography coupled with mass spectrometry (GC/MS) [97], ion chromatography (IC) [98], combustion ion chromatography (C/IC) [99], combustion-microcoulometry, combustion ion chromatography titration [100], ultrasonic extraction-high temperature combustion absorption-ion chromatography [101], neutron activation analysis (NAA) [102,103], inductively coupled plasma mass spectrometry (ICP/MS) [104], inductively coupled plasma atomic emission spectroscopy (ICP/AES) [105], liquid chromatography coupled with mass spectrometry (LC/MS) [106], precursor ion scan of triple quadrupole mass spectrometry (PIS of QqQ MS) [79] and flow injection analysis (FIA) [107,108] have been utilized. The wide application of NAA, GC/MS, LC/MS, ICP/MS and ICP/AES is not regulated by legislation because of the high cost and skill level required.…”
Section: Determination Of Aoxmentioning
confidence: 99%
“…For example, centrifugation and drying are used in the analysis of sludge as treatment procedures. In [97], the authors demonstrated that these procedures have a significant influence on the elimination of AOX because near 50-80% of them remain in the sludge, which means that 20-50% are extracted from the sample.…”
Section: Determination Of Aoxmentioning
confidence: 99%
See 1 more Smart Citation